PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN BOGOR - Jati Adam; Bambang Sutarto (Jurnal Menara, 2025)
This study aims to determine the effect of discipline and work environment on employee performance at the Bogor Regency Ministry of Religion Office. The method used is a quantitative method. This data collection technique is carried out by taking objects from a sample called sampling or respondents, the sampling method using a saturated sample technique with 88 respondents. The data analysis method used is an instrument test consisting of a validity test, a reliability test, a classical assumption test consisting of a normality test, a multicollinearity test, a heteroscedasticity test, a multiple linear regression test, a simple linear regression test, a correlation coefficient, a determination coefficient test, a hypothesis test consisting of a partial t test and a simultaneous f test. From the results of this study it can be concluded that discipline has a positive and significant effect on employee performance with a label t-count value or or (17.490> 1.987), and a significance value of 0.000 <0.050. Thus, H0 is rejected and H1 is accepted. The work environment has a positive and significant influence on employee performance with a label t-value or (22.918 > 1.987) and a significance value of 0.000 < 0.05. Thus, H0 is rejected and H2 is accepted. Discipline and work environment have a positive and significant influence on employee performance with a value of Fcount > Ftable or (321.463 > 3.100) and a significance value of 0.000 < 0.050. Thus, H0 is rejected and H3 is accepted. Discipline and work environment on employee performance have a simple linear regression effect Y = 3.131 + 0.214 (X1) + 0.422 (X2).